Spatial Distribution of Neuropathology and Neuroinflammation Elucidate the Biomechanics of Fluid Percussion Injury - Joshua A. Beitchman; Jonathan Lifshitz; Neil G. Harris; Theresa Currier Thomas; Audrey D. Lafrenaye; Anders H?nell; C. Edward Dixon; John T. Povlishock; Rachel K. Rowe (Neurotrauma Reports, 2021)
Diffuse brain injury is better described as multi-focal, where pathology can be found adjacent to seemingly uninjured neural tissue. In experimental diffuse brain injury, pathology and pathophysiology have been reported far more lateral than predicted by the impact site. We hypothesized that local thickening of the rodent skull at the temporal ridges serves to focus the intracranial mechanical forces experienced during brain injury and generate predictable pathology. We demonstrated local thickening of the skull at the temporal ridges using contour analysis on magnetic resonance imaging. After diffuse brain injury induced by midline fluid percussion injury (mFPI), pathological foci along the anterior-posterior length of cortex under the temporal ridges were evident acutely (1, 2, and 7 days) and chronically (28 days) post-injury by deposition of argyophilic reaction product. Area CA3 of the hippocampus and lateral nuclei of the thalamus showed pathological change, suggesting that mechanical forces to or from the temporal ridges shear subcortical regions. A proposed model of mFPI biomechanics suggests that injury force vectors reflect off the skull base and radiate toward the temporal ridge, thereby injuring ventral thalamus, dorsolateral hippocampus, and sensorimotor cortex. Surgically thinning the temporal ridge before injury reduced injury-induced inflammation in the sensorimotor cortex. These data build evidence for temporal ridges of the rodent skull to contribute to the observed pathology, whether by focusing extracranial forces to enter the cranium or intracranial forces to escape the cranium. Pre-clinical investigations can take advantage of the predicted pathology to explore injury mechanisms and treatment efficacy.